PENGELOLAAN KAS KECIL PADA PERCETAKAN SURYA MANDIRI TANGERANG - Ermanuri Ermanuri; Dandi Heryanto Saputra (POLITEKNIK LP3I JAKARTA, 2021)
This research was conducted at Surya Mandiri Printing located in Tangerang area. The purpose of this research is to find out what methods are applied in the management of petty cash in Surya Mandiri Printing, to find out how to manage petty cash, and to know the accounting records of transactions related to petty cash at Surya Mandiri Printing. While the research methodology in this study is descriptive. Based on research it can be concluded that the method used for the management of petty cash in Surya Mandiri Printing is a method of non-fixed funds (fluctuation fund system), then for petty cash expenditures divided into two types, namely direct expenditure and expenditure in cash advance, recharging petty cash erratically, so charging is adjusted to petty cash balances. For petty cash accounting records are done by small cash holders who record to petty cash records then the accounting section will extend to excel and posted into petty cash ledger. The process is still done manually, namely with Microsoft Excel and has not used accounting software.Keywords: Management, Petty Cash